2016
DOI: 10.1590/abd1806-4841.20163800
|View full text |Cite
|
Sign up to set email alerts
|

Linear cutaneous lupus erythematosus following the lines of Blaschko - Case report

Abstract: Chronic cutaneous lupus erythematosus in a linear configuration is rare, particularly in children, demonstrating similar incidence in both genders, no photo-sensitivity and lower probability of progression to systemic disease. We describe the case of a 9-year-old girl who presented erythematous papules with central atrophy on the upper and lower right limbs, asymptomatic and following the lines of Blaschko, since age four. Histological examination showed atrophy of the epidermis with aggression from epidermal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…These findings are granular depositions of IgG, IgM, IgA, and/or C3 along the dermoepidermal junction and periadnexal structure. Nonetheless, a negative DIF result does not exclude the diagnosis [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are granular depositions of IgG, IgM, IgA, and/or C3 along the dermoepidermal junction and periadnexal structure. Nonetheless, a negative DIF result does not exclude the diagnosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature review, a total of 102 cases diagnosed with LCLE have been reported. The most common pathological diagnosis of CLE in the linear distribution was discoid lupus erythematosus (DLE) (39.2%), followed by lupus erythematosus panniculitis (LEP) (21.6%), lupus erythematosus tumid (LET) (2.9%), subacute lupus erythematosus (SCLE) (2%) and bullous lesions of SLE (1%) [4][5][6][7][8][9][10][11][12][13]. LDLE mainly occurs in children and young adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LBLE has recently been proposed as a prominent subset of linear cutaneous lupus erythematosus in children . Its distinct features include early onset (children and young adults), equal incidence in both sexes, skin lesions showing a blaschkoid distribution predominantly in the head and neck, low photosensitivity, and absence of antibodies . Histologically, it appears identical to cutaneous LE, especially discoid and panicullitic LE.…”
mentioning
confidence: 99%